2022
DOI: 10.3389/fphar.2022.894963
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate Therapy Alleviates Fracture-Associated Chronic Pain After Orthopedic Surgery by Suppressing CCL21-Dependent TREM2/DAP12 Inflammatory Signaling in Mice

Abstract: Chronic pain after bone fracture and orthopedic surgery is often refractory to most analgesics currently in use, thus emphasizing the urgent need for improved therapeutic medications. Chemokine-dependent neuroinflammation is critical for excitatory synaptic plasticity and central nociception sensitization. Recent studies have focused on the inhibition of inflammatory responses by artesunate, the first anti-malaria drug extracted from artemisinin. The present study investigated the analgesic effects and potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In general, expression variations in chemokines and their receptors in the spinal dorsal horn are a key step for the pathophysiology of fracture-caused chronic allodynia developments [ 24 , 25 , 26 ]. Elisa analyses represented a considerable elevation in the protein levels of CXCL1 and its receptor CXCR2 on day 7 following fracture procedures in mice ( p < 0.05, n = 4, one-way ANOVA; Figure 2 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, expression variations in chemokines and their receptors in the spinal dorsal horn are a key step for the pathophysiology of fracture-caused chronic allodynia developments [ 24 , 25 , 26 ]. Elisa analyses represented a considerable elevation in the protein levels of CXCL1 and its receptor CXCR2 on day 7 following fracture procedures in mice ( p < 0.05, n = 4, one-way ANOVA; Figure 2 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay (ELISA) was used to measure the concentrations of CXCL1 (Abcam, UK), and CXCR2 (Wuhan Fine Biotech Co., Wuhan, China) in the L4-5 levels of left spinal cord [ 24 ]. Spinal cord tissues were homogenized in a lysis buffer containing protease and phosphatase inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…The triggering receptor expressed on myeloid cells 2 (TREM2) forms a receptor complex with DNAX-activating protein of 12 kDa (DAP12) on the plasma membrane of microglia and induces the activation of microglia via DAP12, which, in turn, is involved in the induction and maintenance of neuropathic pain [ 70 ]. Based on the studies described above, we found [ 71 ] that exposure of the spinal cord to CCL21 upregulates TREM2 and DAP12 expression, and pharmacological inhibition of TREM2/DAP12 ameliorates CFP and CCL21-induced acute pain. These results suggest that inhibition of CCL21-dependent TREM2/DAP12 neuroinflammatory signaling may have a previously undescribed role in alleviating CFP.…”
Section: Molecules Involved In Cfp and Their Mechanisms Of Actionmentioning
confidence: 99%
“…Kallikrein is essentially a proteolytic enzyme that produces bradykinin (BK), a related peptide (Lys-BK), and its active metabolites from kininogen substrates [ 72 ]. Kinin is involved in the regulation of inflammatory processes by activating two G protein-coupled receptors, B1 and B2 [ 71 ]. B1R, encoded by the gene BDKRB1, is rarely expressed in healthy tissue, and its expression is only induced under specific conditions such as injury and inflammation, whereas B2R is expressed continuously [ 73 ].…”
Section: Molecules Involved In Cfp and Their Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation